Impact of Low-Dose Amino Acid-Chelated Trace Minerals on Performance, Antioxidant Capacity, and Fecal Excretion in Growing-Finishing Pigs - Yunxia Xiong; Fei Zhao; Yaojie Li; Qiwen Wu; Huaqin Xiao; Shuting Cao; Xuefen Yang; Kaiguo Gao; Zongyong Jiang; Shenglan Hu; Li Wang (Animals)
Our previous study has shown that replacing 100% inorganic trace minerals with 30% amino acid-chelated ones can enhance antioxidant capacity, improve nutrient digestibility, and reduce fecal excretion in growing-finishing pigs without compromising performance. This study aimed to further reduce the amino acid-chelated trace minerals content in pig diets and assess its impact. Seventy-two growing-finishing barrows (Duroc × Landrace × Yorkshire), with an initial average body weight of 67.04 ± 0.12 kg, were divided into four groups: negative control (NC, no additional trace minerals), high-dose inorganic trace minerals (HITM, 100% inorganic; 75 mg/kg Fe, 10 mg/kg Cu, 65 mg/kg Zn, 25 mg/kg Mn), and two low-dose groups (15 mg/kg Fe, 4 mg/kg Cu, 12.5 mg/kg Zn, 5 mg/kg Mn) receiving either inorganic sulfates (LITM) or amino acid-chelates (LOTM). The trial concluded when the body weight of pigs reached ~130 kg. Results showed that low-dose trace mineral substitution did not adversely affect growth performance, carcass traits, meat quality, or nutrient digestibility in growing-finishing pigs (p > 0.05). The LOTM pigs exhibited significantly higher serum glutathione peroxidase, liver total superoxide dismutase (T-SOD), and CuZn-SOD activities, muscle CuZn-SOD and catalase activities, and lower liver malondialdehyde content compared with LITM (p < 0.05). Muscle CuZn-SOD in LITM was lower than HITM (p < 0.05), but not in LOTM (p > 0.05). LOTM showed significantly higher muscle Fe content and lower muscle Mn content compared with HITM (p < 0.05), yet its muscle Mn level was higher than that of LITM (p < 0.05). Liver Zn content decreased in LITM compared with HITM (p < 0.05), but remained unchanged in LOTM (p > 0.05). Both LITM and LOTM significantly reduced fecal emissions of Fe, Cu, Zn, and Mn compared with HITM (p < 0.05), with greater reductions in Cu, Zn, and Mn in LOTM. In conclusion, low-dose substitution of inorganic or organic trace minerals did not negatively affect growth, carcass traits, meat quality, or nutrient digestibility in growing-finishing pigs, while it effectively reduced fecal heavy metal emissions. Organic trace minerals were more effective in enhancing antioxidant activity and trace mineral deposition.